Analisis Praktik Pendidikan di Kampung Naga Berdasarkan Konsep Tripusat Pendidikan Ki Hajar Dewantara - Yuda, Erlangga Kusuma; Nuryani, Nuryani; Rosmilawati, Ila (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Education is one of the key aspects in the development of a society. Among them, it functions to build society, create cultural transformation, produce skilled workers, create tools for social control. However, there is moral degradation in society, including; The rise in cases of corruption, non-compliance with the law, violence and bullying, intolerance between religions, ethnicities and groups indicates that there are problems in education in society. This phenomenon is very rarely found in Kampung Naga. This is the background to this research. The aim is to analyze what educational practices exist in Kampung Naga using Ki Hajar Dewantara's tricenter theory of education. The research method used is ethnography and is complemented by literature study. The results of this research suggest that all educational practices in the village have a synergy of the three elements; be it family, school and community.Â  From these educational practices, the people of Kampung Naga have succeeded in maintaining their identity. Maintaining the culture and customs that have been passed down from our ancestors. And can prevent the influence of foreign cultures and strange trends that develop on social media.Â